Family Reform and Judicial Discretion of the judge to resolve family disputes - Busboos, Fawzieh Salem Mubarak (Journal of Economic, Administrative and Legal Sciences, 2020)
Family reform and judicial discretion of the judge to resolve family disputes are one of the most important ways to protect the continuity and cohesion of the family، Islam has given the family a central place in society and has given it great care in terms of its foundation on the requirements of religion as well as in terms of its continuity on a solid foundation of intimacy and compassion. Islam as a realistic religion didn’t rule out exposing this family for a series of conflicts that threaten its stability. Therefore، Islam urged to reform between the spouses whenever there is a disagreement between them. Islam gave the judge a judicial discretion in resolving family disputes. Jordanian Personal Status Law didn’t deviate from what is prescribed in Islamic jurisprudence، where the judge was given a judicial discretion in resolving family disputes، A judicial discretion is the freedom that left by the law to a judge either expressly or implicitly، This is in order to choose the most appropriate and the closest solution among other solutions. We have concluded that one of the most important factors for the success of the judge in reducing family disputes is providing appropriate conditions for effort and reform attempts.